Determinants of Trust Towards Tourist Destinations - Marinao-Artigas, E (Elsevier Ltd, 2017)
Trust has become a relevant concern for tourist destinations. Partly because of the novelty of the research on trust in the tourism literature, there are several open questions regarding the antecedents of trust towards a tourist destination. In this research, we suggest that reputation, and cognitive and affective evaluation of a destination, are relevant antecedents of trust. Trust towards a tourist destination is understood as a multidimensional construct, including local inhabitants and public and private institutions that are honest, benevolent and competent. This paper used a non-probabilistic sample of 750 tourists based on quotas, proportionally distributed among the main tourist destinations in Chile. After testing the psychometric properties of the scales developed for this study, a structural equation model was estimated and it was found that trust is a consequence of the reputation of the destination, as well as the cognitive and affective evaluation of the tourists. The paper concludes by emphasising the importance of these findings for the tourism industry, and outlines recommendations to reinforce trust relations with tourists. © 2017 Elsevier Ltd